Prevention of Website SQL Injection Using a New Query Comparison and Encryption Algorithm - Baklizi, Mahmoud; Atoum, Issa; Al-Sheikh Hasan, Mohammad; Abdullah, Nibras; Al-Wesabi, Ola A.; Otoom , Ahmed Ali (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Nowadays, a web application has become necessary in all organizations. Which deals directly with the databases in which data and information are stored, organized, retrieved, and processed. Therefore, most of its attacks are on databases. Therefore, web applications must be secure enough to prevent access to customs databases, destruction, and theft of bank accounts and transactions. Thus, most SQL injection attacks are carried out through character spacing, as it is the tool used by hackers to find a vulnerability on the web. This paper proposes a new algorithm to prevent hackers from accessing databases early on through the web application without accessing databases. The proposed algorithm is designed to protect the web application from being voluntarily inserted by using a bind parameter, blocking the hacker’s address, and rejecting his request when executing the query. Also, this algorithm is designed to work in more than one layer, as it works at the web application and URL levels so that things are sufficiently protected. The comparison was made with the algorithms SQLPMDS, SIUQAPTT, and blind SQL injection, and the results showed that the presented algorithm gave better results based on more than one measure.